2002
DOI: 10.1177/107755802237808
|View full text |Cite
|
Sign up to set email alerts
|

Access to Medical Care for Low-Income Persons: How do Communities Make a Difference?

Abstract: This paper considers the impact of community-level variables over and above the effects of individual characteristics on healthcare access of low-income children and adults residing in large metropolitan statistical areas (MSAs). Further, we rank MSAs' performance in promoting healthcare access for their low-income populations. The individual-level data come from the 1995 and 1996 National Health Interview Survey (NHIS). The community-level variables are derived from multiple public-use data sources. The outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
158
2
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(178 citation statements)
references
References 26 publications
(17 reference statements)
13
158
2
5
Order By: Relevance
“…We found that the mammography implementation rate increased with income level, from 14.3% of housewives to 55.6% of private sector worker group. Two primary reasons may account for the low implementation rate of mammography in low-income patient groups: first, these individuals may not be able to afford the expense of the examination (Ward et al, 2008;Cunningham et al, 2009); and second, these patients are usually residents of poorer regions in which hospitals are unable to buy advanced mammography equipment (Ferrante et al, 2000;Andersen et al, 2002;Barry et al, 2005). A similar finding was made regarding other types of examinations.…”
Section: Discussionmentioning
confidence: 79%
“…We found that the mammography implementation rate increased with income level, from 14.3% of housewives to 55.6% of private sector worker group. Two primary reasons may account for the low implementation rate of mammography in low-income patient groups: first, these individuals may not be able to afford the expense of the examination (Ward et al, 2008;Cunningham et al, 2009); and second, these patients are usually residents of poorer regions in which hospitals are unable to buy advanced mammography equipment (Ferrante et al, 2000;Andersen et al, 2002;Barry et al, 2005). A similar finding was made regarding other types of examinations.…”
Section: Discussionmentioning
confidence: 79%
“…Uninsured children have less access to primary care and outpatient services, both before admission and after discharge from the hospital. 25 Prior studies, however, found no differences between uninsured and insured children in hospitalization rates, [26][27][28] LOS, [26][27][28] or the quality of asthma management. 29 Another difference could be in the availability of a medical home for children in large urban areas.…”
Section: Discussionmentioning
confidence: 95%
“…Los estudios dilucidaron cuestiones como: los factores que afectan el acceso/utilización de servicios de salud (10,(14)(15)(16)19,21,22,25,27,30,41); las diferencias, desigualdades e inequidades en la utilización de servicios de salud (8,12,17,18,31,32,34,35,37); los roles del seguro en la utilización (9,20,26,28,29); las barreras para el acceso/utilización (11,13,23,24,40); las vivencias y expectativas sobre la utilización (33,38,39) y los patrones de uso (36).…”
Section: Tabla 1 Características De Los Estudiosunclassified
“…Las variables del sistema de salud fueron medidas en 41,9 % de los estudios cuantitativos (8,10,11,13,14,16,19,(23)(24)(25)(26)29,37), encontrándose que los factores más estudiados fueron: disponibilidad de recurso humanos y físicos, tipo de servicios, tiempos de espera para obtener una cita, tiempo de espera en el consultorio y políticas institucionales, respectivamente.…”
Section: Figura 1tipo De Variables Explicativas Del Objeto De Estudiounclassified
See 1 more Smart Citation